2006
DOI: 10.1111/j.1471-0528.2006.01099.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: Vaginal vault smears after hysterectomy for reasons other than malignancy: a systematic review of the literature

Abstract: Background Vaginal vault smears are used to detect persisting neoplasia of the lower genital tract after hysterectomy. Recent data suggest both widespread use and uncertain evidence of their effectiveness.Objectives To identify and synthesise evidence on the use and effectiveness of vaginal vault smears and to assess the quality. Selection criteria Primary research, women who had a hysterectomy and were followed up by vault cytology.Data collection and analysis Systematic search (eight electronic databases), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 44 publications
(119 reference statements)
0
34
0
Order By: Relevance
“…The risk of cancer in young women is quite low, and assessment of changes in cervical cancer rates where comprehensive screening has been initiated suggests that screening has little impact on rare early-onset cancers, especially those presenting before age 25 (10). Screening after hysterectomy for benign indications also is not cost-effective, though still commonly done (11, 12). Overscreening can result in patient harms, including missed work, travel and child care costs, anxiety, stigmatization, and obstetric and surgical complications from treatment of lesions that would not have progressed to cancer (13, 14).…”
Section: Limits To Current Screeningmentioning
confidence: 99%
“…The risk of cancer in young women is quite low, and assessment of changes in cervical cancer rates where comprehensive screening has been initiated suggests that screening has little impact on rare early-onset cancers, especially those presenting before age 25 (10). Screening after hysterectomy for benign indications also is not cost-effective, though still commonly done (11, 12). Overscreening can result in patient harms, including missed work, travel and child care costs, anxiety, stigmatization, and obstetric and surgical complications from treatment of lesions that would not have progressed to cancer (13, 14).…”
Section: Limits To Current Screeningmentioning
confidence: 99%
“…It has been clearly shown that women with CIN3, despite treatment, are at increasing risk of cervical or vaginal cancer at advanced ages, but the specific cancer risk for women who undergo total hysterectomy was not known. There are few studies addressing this issue and they show conflicting results …”
Section: Introductionmentioning
confidence: 99%
“…The reported risk of cervical cancer after subtotal hysterectomy is low, 0.1% to 1.9% [88]. The reported risk of cancer at the vaginal vault is 0.03% in women who undergo total hysterectomy to treat cervical intraepithelial neoplasia 3; there is no reported case of cancer occurring at the vaginal vault after total hysterectomy performed to treat benign indications other than cervical intraepithelial neoplasia [89]. An ACOG guideline reports that women with known or suspected gynecologic cancer, current or recent cervical dysplasia, or endometrial hyperplasia are not candidates for subtotal hysterectomy [90]; however, fear of future cervical stump carcinoma should not discourage those with a history of normal cervical surveillance from undergoing subtotal hysterectomy.…”
Section: Cervical Stump Carcinomamentioning
confidence: 93%